The role of funding the Youth and Sports Welfare Fund in improving the state of Yemeni sports - hoseine alnadhiri, Mohammed (sports creativity, 2025)
The Fund for the Care of children and youth and sports in Yemen, one of the important means which have helped these groups to develop and refine their talents and their creations, before its establishment in 1996 the sport of Yemen lacks the resources to improve the levels in the various games, where he witnessed this sector before this period, a dearth of sports facilities, and lack of preparations in the clubs and teams, and not embrace the State Championships, has changed as much as the sports sector has witnessed steady growth both in terms of infrastructure or the preparation of young people. The objective of this research to identify the position occupied by the children and youth in the community., And monitor the overall achievements of the Fund, and identify the challenges and difficulties faced by them, and make appropriate recommendations to address them. And the researcher to the existence of a legislative environment good about interest the government of Yemen, the most important fund-care children and youth and sports, which contributed to the creation of numerous clubs and sports associations, and show that the ill conduct of successive administrations was the latest large deficit in its budget, by not constant follow up to those responsible for pay their fees according to the law passed by them